Case report: Microsatellite instability determination is not always black and white in Lynch syndrome diagnosis - Rodriguez, Julieta E.; Vasseur, Damien; Bani, Mohamed Amine; Cabaret, Odile; Cotteret, Sophie; Muleris, Martine; Golbarg, Veronica; Malka, David; Pudlarz, Thomas; Caron, Olivier; Smolenschi, Cristina (Frontiers in Oncology, 2024)
Introduction Microsatellite instability (MSI) is a genetic marker that is useful in the detection and treatment of Lynch syndrome (Sd). Although conventional techniques such as immunohistochemistry (IHC) and polymerase chain reaction (PCR) are the standards for MSI detection, the advent of next-generation sequencing (NGS) has offered new possibilities, especially with circulating DNA. Case report We present the case of a 26-year-old patient with Lynch Sd and a BRAF-mutated metastatic colon cancer. The discordant MSI results between the conventional methods and NGS posed challenges in making treatment decisions. Subsequent NGS analysis revealed a high MSI status, leading to participation in an immunotherapy trial, with remarkable clinical response. Conclusion This case emphasizes the importance of comprehensive molecular profiling and strong interdisciplinary collaborations, especially in cases with ambiguous MSI results.